Politicized Scientists: Credibility Cost of Political Expression on Twitter - Eleonora Alabrese; Francesco Capozza; Prashant Garg (CESifo GmbH, 2024)
The study measures scientists' polarization on social media and its impact on public perceptions of their credibility. Analyzing 98,000 scientists on Twitter from 2016 to 2022 reveals significant divergence in expressed political opinions. An experiment assesses the impact of online political expression on a representative sample of 1,700 U.S. respondents, who rated vignettes with synthetic academic profiles varying scientists' political affiliations based on real tweets. Politically neutral scientists are viewed as the most credible. Strikingly, on both the 'left' and 'right' sides of politically neutral, there is a monotonic penalty for scientists displaying political affiliations: the stronger their posts, the less credible their profile and research are perceived, and the lower the public's willingness to read their content. The penalty varies with respondents' political leanings.
Keywords: A11; C93; D72; D83; D91; I23; Z10; Z13; 330; Twitter; trust in science; ideological polarization; affective polarization; online experiment